Strategi Penanaman Nilai Sila Ke-2 Pancasila Pada Masa Pandemi Covid-19, Oleh Mahasiswa Universitas Pembangunan Nasional Veteran Jakarta - Setiyawati, Marina Ery; Subakdi, Subakdi; Hermina, Hermina; Wahyuningtyas, Widayani (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
This study aims to describe the cultivation of the values of just and cultured humanity to UPNVJ students. Pancasila values are the foundational principles or perspectives in actions, even during the Covid-19 pandemic, these values must be upheld, especially in implementing government policies in the field of education. Lecturers, as essential components of the educational workforce, have the task of facilitating the learning process. Cultivation strategies refer to the methods and art of utilizing resources to achieve specific goals. Planting the values of Pancasila’s second principle in higher education needs to be applied to confront the era of globalization, which witnesses the influx of various new cultures and civilizations from different nations around the world. The implementation of humanitarian values in national and societal life certainly cannot escape violations related to these values. This study employs a quantitative research approach. The subjects of this study are students of the National Veteran Development University Jakarta. Data collection is carried out by distributing questionnaires to the students. The results of this study can be concluded that the cultivation of the values of just and cultured humanity by UPNVJ students predominantly yields highly agreeable results. It is expected that students can instill the values of the second principle of Pancasila, which is the value of just and cultured humanity, in their daily lives.